Pendampingan Kelembagaan dan Manajemen BUMDes Sejahtera Desa Sapelang, Buko Selatan, Kabupaten Banggai Kepulauan - Sululing, Siswadi (Welfare : Jurnal Pengabdian Masyarakat, 2023)
This community service activity was carried out in Sapelang Village, South Buko District, with the topic "Institutional Assistance and BUMDes Management". The purpose of implementing this community service activity is to transfer knowledge and provide solutions to problems faced by prosperous BUMDes. The implementation method used is mentoring, which consists of providing material on BUMDes institutions and BUMDes management, accompanied by practice and evaluation. The results of the practice and evaluation of BUMDes management participants have been understood, so they know the main duties and responsibilities of each based on a clear organizational structure and understand making standard operating procedures and BUMDes management consisting of planning, organizing, implementing, and supervising thanks to practice and answering questions correctly. There are suggestions that this activity should be carried out for about 1-2 days in order to achieve maximum results.